PHYTOCHEMICAL STUDIES OF SIAM QUEEN (THAI BASIL) PLANT EXTRACT (International Journal of Food and Nutritional Sciences, 2023)
Medicinal herbs have been utilized for thousands of year for different purpose such as herbal remedies, prescription drugs, and alternative medicines. Most Phytochemicals present in plant like carotenoids, flavonoids, and polyphenols have antimicrobial activity and serve as a source of antimicrobial agents. In this research we used one medicinal plant of basil family which is Ocimum basilicum var. thyrsiflora common name Siam queen (Thai Basil). Siam queen contain many kinds of phytoconstituents which act as antimicrobial agent